2000
DOI: 10.1177/155005940003100310
|View full text |Cite
|
Sign up to set email alerts
|

Nose Wiping: An Unrecognized Automatism in Absence Seizures

Abstract: Nose wiping is a well-known postictal automatism in complex partial seizures, considered very important for lateralization. We report a 24-year-old woman selected from 32 patients with video-EEG investigations of absence seizures. The patient, with normal examination and imaging findings, had typical absence seizures from the age of 5 years, which were controlled with either ethosuximide or valproate and worsened by carbamazepine. In two of her recorded typical absence seizures associated with generalized 3 Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…They are less common in patients with extratemporal onset seizures and we reported that they also accompany absence seizures (32,33). Activation of the central autonomic network, particularly the amygdala, is thought to lead to nasal secretion.…”
Section: Peri-ictal Respiratory Changesmentioning
confidence: 79%
“…They are less common in patients with extratemporal onset seizures and we reported that they also accompany absence seizures (32,33). Activation of the central autonomic network, particularly the amygdala, is thought to lead to nasal secretion.…”
Section: Peri-ictal Respiratory Changesmentioning
confidence: 79%
“…The results of this study do not support the hypothesis that post-pubertal females are more susceptible than males to the aggravating effect of CBZ on absence seizures. This hypothesis was based primarily on the clinical observation that most of the reported post-pubescent patients have been pre-menopausal women 7,[11][12][13][14][15][16] . This observation may instead reflect a selection bias as a result of absence seizures in adulthood being more common in females than males.…”
Section: Discussionmentioning
confidence: 99%
“…There is clinical evidence that there may be a sex difference in the susceptibility of post-pubescent patients to the aggravation of absence seizure by CBZ, with the vast majority of such reported cases being pre-menopausal women 7,[11][12][13][14][15][16] . Furthermore, absence seizures persisting into adulthood are more common in females, and the frequency of absence epilepsy in adults is positively correlated with progesterone levels 17 .…”
Section: Introductionmentioning
confidence: 99%